Single-Nucleotide Polymorphisms and Haplotypes of Intercellular Adhesion Molecule-1 in Uterine Cervical Carcinogenesis in Taiwanese Women. (March 2016) - Sun, Yi-Hung; Yang, Shun-Fa; Liu, Yu-Fan; Ko, Jiunn-Liang; Wu, Chih-Hsien; Wu, Tzu-Fan; Wang, Po-Hui
The association of intercellular adhesion molecule 1 ( ICAM-1 ) genetic polymorphisms with uterine cervical carcinogenesis has seldom been reported. Therefore, the aim of this study was to investigate the association of single-nucleotide polymorphisms (SNPs) and haplotypes of ICAM-1 with cervical tumorigenesis in Taiwanese women. Four hundred forty four women, including 91 with cervical invasive cancer, 63 with precancerous lesions, and 290 normal controls, were recruited. The genotypic distribution of 4 SNPs of ICAM-1, rs5498 (A1548G), rs5491 (K56M), rs281432 (C8823G), and rs3093030 (C-286T) was determined using real-time polymerase chain reactions and genotyping. Compared to homozygous wild CC, heterozygous CG, homozygous mutant GG, or genotypes with CG/GG display increased risks or a tendency of precancerous lesions or invasive cancer with strong power in rs281432. The homozygotic mutant alleles TT in rs3093030 and homozygotic mutant alleles GG in rs5498 were associated with a higher risk of invasive cancer and precancerous lesions, respectively, but with lower power. The CG/TA/TG haplotypes of ICAM-1 SNPs rs3093030 and rs5498 exhibited a tendency to increase susceptibility to precancerous lesions and invasive cancer. In conclusion, Taiwanese women with ICAM-1 SNP rs281432 and haplotypes CG/TA/TG of rs3093030 and rs5498 are associated with uterine cervical carcinogenesis.